Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials: International Scientific Conference, 3-8 November 2014, Tomsk, Russia; [proceedings]; IOP Conference Series: Materials Science and Engineering (2015, 2015)
Title screen